Pengaruh Return on Asset, Net Profit Margin, dan Earning Per Share Terhadap Harga Saham Perusahaan Rokok Go Public - Andriyanto, Irsad; Khoirunnisa, Silvia (AKTSAR: Jurnal Akuntansi Syariah, 2018)
This study aimed to investigate empirically influence the company characteristics proxied by return on assets, net profit margin, and earning per share on the stock price of cigarette companies listed in IDX. The Investment was the decision taken to allocate assets in order to get benefit in the future. This study was explanatory research using a quantitative approach to analyze the sample of cigarette companies listed in IDX from 2015 to 2017. The data are taken from IDX then analyzed by multiple linear regression analysis supported by SPSS. The results showed that the return on assets and earnings per share did not have a significant influence on the stock price. Moreover, the net profit margin was the most influential variable on stock prices. Net profit margin showed a high level of efficiency, so it became an important factor that the company should consider because of its significant impact on the stock prices.